Recent Advances in the Application of CRISPR/Cas9 Gene Editing System in Poultry Species - Khwatenge, Collins N.; Nahashon, Samuel N. (Frontiers in Genetics, 2021)
CRISPR/Cas9 system genome editing is revolutionizing genetics research in a wide spectrum of animal models in the genetic era. Among these animals, is the poultry species. CRISPR technology is the newest and advanced gene-editing tool that allows researchers to modify and alter gene functions for transcriptional regulation, gene targeting, epigenetic modification, gene therapy and drug delivery in the animal genome. The applicability of CRISPR/Cas9 system in gene editing and modification of genomes in the avian species is still taking flight. Up to date, substantial progress in using CRISPR/Cas9 technology has been made in only two poultry species (chicken and quail), with chicken taking the lead. There have been major recent advances in modification of avian genome through their germ cell lineages. In the poultry industry, breeders and producers can utilize CRISPR-mediated approaches to enhance many required genetic variations towards the poultry population that are absent in a given poultry flock. Thus, CRISPR allows the benefit of accessing genetic characteristics that cannot otherwise be used for poultry production. Therefore CRISPR/Cas9 becomes a very powerful and robust tool for editing genes that allows the introduction or regulation of genetic information in the poultry genomes. However, the CRISPR/Cas9 technology has some several limitations that need to be addressed to enhance its use in the poultry industry. This review will evaluate and give a summary of recent advances in applying CRISPR/Cas9 gene editing technology in poultry research and explore its potential use to advance poultry breeding and production with a major focus on chicken and quail. This would aid future advancements in the usability of CRISPR technology to improve poultry production.